The Role of Cytokines in Predicting the Efficacy of Acute Stage Treatment in Patients with Schizophrenia - He X (Dove Medical Press, 2020)
Xiaoyan He, 1 Qingyan Ma, 1 Yajuan Fan, 1 Binbin Zhao, 1 Wei Wang, 1 Feng Zhu, 2 Xiancang Ma, 1 Lina Zhou 1 1Department of Psychiatry, The First Affiliated Hospital of Medical College of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Center for Translational Medicine, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Lina ZhouDepartment of Psychiatry, The First Affiliated Hospital of Medical College of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of ChinaEmail zhoulinapsy@xjtu.edu.cnPurpose: Inflammatory response in schizophrenia (SCz) is related to its underlying pathological mechanism and might be significant in deciding a patient’s prognosis. The current study aims to investigate the differences in the serum inflammation level between schizophrenic patients and healthy controls and identify inflammatory markers that can predict clinical therapeutic effects in early-stage SCz patients at the 6-month follow-up.Patients and Methods: In total, 71 subjects were recruited in this study, including 35 patients with Scz and 36 healthy controls. The 35 Scz patients, who were in the first-episode or acute relapse state at admission, had completed the 6-month follow-up. The Positive and Negative Syndrome Scale (PANSS) and the Clinical Global Impression (CGI) assessment results, demographic details, and blood samples were collected at the baseline and at follow-up. Data were analyzed using the Spearman correlation and multiple linear regression.Results: Serum interleukin (IL-1β, IL-4, IL-6, and IL-8) levels were significantly elevated in SCz patients at baseline compared with healthy controls, with a reduced IL-8 level at the follow-up. Furthermore, a higher IL-6 level and lower IL-8 level was found to predict better improvement in negative symptoms. The higher IL-6 level also predicted lesser improvement in depressive symptoms. Finally, a higher interferon (IFN)-γ level predicted a lower therapeutic effect for excitatory symptoms.Conclusion: The serum levels of inflammatory markers were higher in patients with SCz than in healthy controls. These markers can be considered accurate predictors of therapeutic effects in patients with SCz.Keywords: schizophrenia, cytokines, therapeutic effect, IL-6, IL-8